Epidemiology of ocular trauma in limited-resource settings: a narrative review - Jessica Pelletie; Kakande Reaga; Sarah McLeo; Noah Kronk; Kamoga Dickson; Kyle Ohman; Matthew Santo (Frontiers in Medicine, 2025)
Ocular trauma disproportionately impacts low- and middle-income countries (LMICs) and contributes significantly to blindness and disability in these settings. While numerous publications address the epidemiology of ocular trauma in limited-resource settings, there are no systematic reviews, meta-analyses, or large-scale review articles investigating this topic further. In this article, the authors summarize, compare, and contrast the extant literature on ocular trauma in LMICs. With this synthesis of the available data, the article aims to identify commonalities and potential targets for systemic change in preventing ocular injury and its associated morbidity. The authors seek to highlight modifiable risk factors which may be addressed by providers, health care systems, government agencies, and employers alike.
Keywords: ocular trauma; emergency medicine; limited resource; low resource settings; low income and middle-income countries; epidemiology